Sosialisasi Pemanfaatan Open Broadcaster Software (OBS) untuk Pembuatan Media Pembelajaran bagi Ustadz di Pondok Pesantren Ar-Royyan - Muh Nur Luthfi Azis; Moch Yusuf Asyhari; Estuning Dewi Hapsari; Ayunda Nur Hapsari (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
The Ar-Royyan Islamic boarding school is a multi-level Islamic educational institution with a focus on preparing graduates who are ready to synergize with the society. To attain this objective, it is imperative to have educational personnel well-versed in the field of information technology. One strategic approach involves training Ustadz and prospective Ustadz through digital learning innovations. Open Broadcast Software (OBS) emerges as an innovative choice for crafting learning materials because it supports various media sources and offers user-friendly settings. Participants can combine video recordings, video from cameras, text, images, sound, and so on the types of input received. The resulting output manifests in the form of the videos available in common formats such as MKV, MOV, FLV, MP4, and MPEG-TS. Evaluation was conducted using a pre-test and post-test, consisting of a response questionnaire and Likert scale. The results indicate an enhanced understanding of OBS among participants, employed in the creation of digital learning media. The majority of participants responded positively to the conducted activities. Several elements that need attention in promoting the use of OBS for learning media creation include color selection, motivational delivery, and effective word choice. Combining OBS with other editing applications can yield unique variations of learning media, incorporating elements such as images, sound, video, and other supported media editing applications